2009
DOI: 10.3141/2139-02
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Fuel Efficiency of Road Traffic by Characterization of Vehicle-Specific Power and Speed Based on Floating Car Data

Abstract: To evaluate the fuel efficiency of road traffic, an approach that captures the characteristics of road traffic on the basis of floating car data (FCD) is proposed. In existing studies of fuel consumption, parameters such as speed, acceleration, and power demand have been adopted to represent the characteristics of traffic flows and vehicle activities. However, they are not suitable for use in the evaluation of fuel efficiency in a dynamic traffic network with various advanced traffic management alternatives. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…The temperature in the SCR system was determined by two factors, including the input heat generated by the engine with the exhaust entering the SCR and the output lost heat from the SCR system. Regarding the first factor, Song [33] found that the time distribution in VSP bins can well represent the fuel consumption per unit of time. According to the law of conservation of energy, the Atmosphere 2019, 10, 337 8 of 17 fuel consumption is proportional to the amount of heat generated.…”
Section: Temperature Model Developmentmentioning
confidence: 99%
“…The temperature in the SCR system was determined by two factors, including the input heat generated by the engine with the exhaust entering the SCR and the output lost heat from the SCR system. Regarding the first factor, Song [33] found that the time distribution in VSP bins can well represent the fuel consumption per unit of time. According to the law of conservation of energy, the Atmosphere 2019, 10, 337 8 of 17 fuel consumption is proportional to the amount of heat generated.…”
Section: Temperature Model Developmentmentioning
confidence: 99%
“…VSP (kW/ton) is the instantaneous tractive power per unit vehicle mass, as illustrated in Equation (1), which can be derived from the instantaneous vehicle speed and acceleration [42]. Furthermore, the increased availability of floating car data (FCD) in urban transportation networks presents a unique opportunity to develop integrated vehicle emission and network control models [43].…”
Section: Vehicle Emission Model Developmentmentioning
confidence: 99%
“…The second approach focused on the real‐world vehicle activity data collected by on‐board devices such as global positioning system and floating cars . These vehicle activities data reflect the impacts of roadway geometric factors (grade, lane width, etc.)…”
Section: Introductionmentioning
confidence: 99%